How SARS-CoV-2 Transformed the Clinical Laboratory: Challenges and Lessons Learned. (24th June 2021) - Tsai, Jonathan M; Tolan, Nicole V; Petrides, Athena K; Kanjilal, Sanjat; Brigl, Manfred; Lindeman, Neal I; Li, Yen-Der; Tanasijevic, Milenko J; Basu, Sankha S; Melanson, Stacy E F
Abstract: The COVID-19 pandemic has made a devastating impact on global health and continues to challenge healthcare infrastructure and delivery. The clinical laboratories were no exception as they are responsible for diagnostic testing that dictates many clinical, infection control, and public health decisions. Information technology and laboratory management tools are critical assets for maintaining and adapting operations in response to crises. When utilized effectively, they promote the integration between the clinical laboratory specialties (e.g., chemistry, hematology, microbiology, and molecular pathology). During the COVID-19 pandemic, our systems and processes were strained due to high testing volumes, demand for rapid turnaround times, supply chain constraints, and constantly evolving testing algorithms and result interpretations as our knowledge of the virus and of diagnostics increased over time. In this report, we describe those challenges and subsequent adaptations made by each clinical laboratory section. We hope these details help to provide potential solutions and approaches for other hospitals facing COVID-19 surges or other future pandemics.